VD_FINDINFO HC / 2011 / 415 vom 8. August 2011 - VD Tribunal cantonal (2011)
DÉCISION D'IRRECEVABILITÉ, AUTORITÉ DE CONCILIATION, ACTE DE RECOURS | 319 let. a CPC (CH), 59 al. 1 CPC (CH), 59 al. 2 let. d CPC (CH)